2013
DOI: 10.2466/16.03.pr0.113x29z3
|View full text |Cite
|
Sign up to set email alerts
|

Finding Workers, Offenders, or Students Most at-Risk for Violence: Actuarial Tests save Lives and Resources

Abstract: 147 adults (107 men, 40 women) and 89 adolescents (61 boys, 28 girls), selected randomly from referrals and volunteers, were given the Ammons Quick Test (QT), the Beck Suicide Scale (BSS), the Minnesota Multiphasic Personality Inventory Second (MMPI-2) or Adolescent Versions (MMPI-A), the Raven's Advanced Progressive Matrices, and the Standard Predictor (SP) of Violence Potential Adult or Adolescent Versions. The goals were to: (a) demonstrate computer and paper-and-pencil tests correlated; (b) validate tests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…See Figure 1 for a comparison of the current ways contrasted with MLIT. There are paper-and-pencil tests, interviews and judgment, medical exams, and the modern MLIT: (a) the paper-and-pencil, violence risk tests, have a mean sensitivity and specificity of .73 [as contrasted with a miss rate of 27%] (Quinsey, Harris, Rice, and Courmier, 1998, 2015Hanson and Thornton, 2000;Monahan et al, 2000); the background-credit checks hit rate is .25 [as compared with a miss rate of 75%] (Quinsey, Harris, Rice, and Cormier, 1998;2015); (b) the interviews and judgment, have an average hit rate of .46 (as opposed to a miss rate of .54) [Sepejak, Menzies, Webster, and Jensen, 1983;Lidz, 1993;Monahan, 1996;Rice, Harris, and Quinsey, 1996]; (c) in 2,200 medical and psychiatric exams, there is a mean .49 hit rate [versus a miss rate of 51%, which exceeds chance] (Hsieh, Gutman, and Haliscak, 2000;Loke, Liaw, Tiong, Ling, and Chang, 2002;Madan and Harley, 2003;Bueno-de-Mesquita, Nuyten, Wesseling, van Tinteren, Linn, and van de Vijver, 2009;Zagar, Kovach, Basile, Hughes, Grove, et al, 2013); and (d) the Standard Predictor of Violence Potential, along with the MMPI-2/A, have a combined specificity and sensitivity for deception, mental illness, substance abuse and violence of 0.97 (Zagar and Grove, 2010;Zagar, Kovach, Basile, Hughes, Grove, et al, 2013) for homicidal, overdosing-substance-abusing, sex-offending and suicide-completers.…”
Section: Contrast Of the Current Ways Of Assessment Vs Mlit Actuariamentioning
confidence: 99%
See 2 more Smart Citations
“…See Figure 1 for a comparison of the current ways contrasted with MLIT. There are paper-and-pencil tests, interviews and judgment, medical exams, and the modern MLIT: (a) the paper-and-pencil, violence risk tests, have a mean sensitivity and specificity of .73 [as contrasted with a miss rate of 27%] (Quinsey, Harris, Rice, and Courmier, 1998, 2015Hanson and Thornton, 2000;Monahan et al, 2000); the background-credit checks hit rate is .25 [as compared with a miss rate of 75%] (Quinsey, Harris, Rice, and Cormier, 1998;2015); (b) the interviews and judgment, have an average hit rate of .46 (as opposed to a miss rate of .54) [Sepejak, Menzies, Webster, and Jensen, 1983;Lidz, 1993;Monahan, 1996;Rice, Harris, and Quinsey, 1996]; (c) in 2,200 medical and psychiatric exams, there is a mean .49 hit rate [versus a miss rate of 51%, which exceeds chance] (Hsieh, Gutman, and Haliscak, 2000;Loke, Liaw, Tiong, Ling, and Chang, 2002;Madan and Harley, 2003;Bueno-de-Mesquita, Nuyten, Wesseling, van Tinteren, Linn, and van de Vijver, 2009;Zagar, Kovach, Basile, Hughes, Grove, et al, 2013); and (d) the Standard Predictor of Violence Potential, along with the MMPI-2/A, have a combined specificity and sensitivity for deception, mental illness, substance abuse and violence of 0.97 (Zagar and Grove, 2010;Zagar, Kovach, Basile, Hughes, Grove, et al, 2013) for homicidal, overdosing-substance-abusing, sex-offending and suicide-completers.…”
Section: Contrast Of the Current Ways Of Assessment Vs Mlit Actuariamentioning
confidence: 99%
“…Zagar and Grove (2010) with N=2,722 showed that homicide, sex offending, and assault was predicted accurately and precisely (AUC for 1,595 adults = .99, AUC for 1,127 youth =.91 and AUC = .96 for 2,722 combined). Zagar, Kovach, Basile, Hughes, Grove et al, 2013, andZagar, et al, 2016 showed that MLIT, actuarial assessment is more objective, reliable, sensitive, specific and valid, than current approaches with .97 vs .39, for homicide, sex-offending and suicide. In a 50 year meta-analysis of suicide research, Franklin, Fox, Bentley, Kleiman, Huang, et al, (2017) discovered that MLIT was superior to find risk factors for suicidal thoughts and behavior.…”
Section: Mlit Actuarial Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…This method will be discussed. The second method, the case study approach with statistical (actuarial) testing, has been discussed in Zagar, Kovach, Basile, Hughes, Grove, Busch, et al , 2013, (in review) and will not be further mentioned here. The regression equation to identify risk-prone teens has a proven track record of predicting which youths may become violent, compared with those less likely to commit offenses against persons.…”
Section: Identification Of Violence-prone Personsmentioning
confidence: 99%
“…Over 35 years, annual workplace homicides dropped from 1,000 to 400; 25% of yearly workplace homicides were due to robberies. If one included just off-the-work-site murders, these annual work place homicide rates doubled to 800 (Zagar, Kovach, Basile, et al, 2013). With more jobs, homicides decrease.…”
mentioning
confidence: 99%